Improving public health by respecting autonomy: Using social science research to enfranchise vulnerable prison populations - Shaw, David; Elger, Bernice (Preventive medicine, 2015)
It is widely recognised that prisoners constitute a vulnerable population that is subject to numerous health inequalities and merits special protection. Improving prisoners' access to healthcare by ensuring adherence to the principle of equivalence has been the main focus of efforts to ensure that their health is not jeopardised. However, another means of respecting prisoners' autonomy and improving their health is to involve them (and prison staff) in social science research within prisons. Such research not only produces valuable data which can be used to assess whether the principle of equivalence is being respected; it also enfranchises prisoners by allowing them to air concerns about perceived ill-treatment and influence their environment. If prison authorities enable such research and adjust policy accordingly, both they and prisoners will benefit from the increased level of respect for prisoners' autonomy, and the improvements in individual and public health that flow from this. Conducting social science research in prisons enables the creation of a virtuous cycle of respect that makes prisons safer and healthier places. •Social science research can provide evidence that may improve prisoners' health.•It can also enfranchise inmates by letting them air concerns about ill-treatment.•It enables creation of a virtuous cycle of respect that makes prisons safer places.